Cutting reduces variation in biomass production of forage crops and allows low‐performers to catch up: A case study of Trifolium pratense L. (red clover). (26th February 2018) - Herbert, D. B.; Ekschmitt, K.; Wissemann, V.; Becker, A.
Abstract: Re‐growth of fodder plants after grazing and mowing drives the profitability of their cultivation and is therefore an important target trait for plant breeding and agricultural engineering. However, for some fodder plants little is known about their re‐growth dynamics in response to grazing or mowing. We analysed the native response of plant architecture, leaf morphology and growth performance to experimental cutting in wild Trifolium pratense L. (red clover) plants. A total of 150 potted clover plants were established under controlled field conditions, and half of the plants were cut to 5 cm 3 months after sowing. Each plant was measured every week for 5 months. The cut and subsequently re‐grown plants carried fewer main branches (−20%), as well as fewer (−13%) and smaller (−32%) leaves than the control plants. However, the cut plants produced an average of 17% more accumulated leaf area (cut + re‐grown leaf area) than the control plants. This discrepancy was explained by variation in the growth strategy of the plants, where the cut plants invariably expressed a second growth phase, while almost half of the untreated plants did not. Our results suggest that cutting acted as an artificial trigger initiating a second growth phase in the cut plants and thereby contributed to yield increase. Exploiting this mechanism may set new goals for breeding and optimisation of the mowing regime.